Fast-track Pathway for Minimally Invasive Colorectal Surgery with and without Alvimopan (Entereg)™: Which is More Cost-effective?. Issue 6 (June 2013) - Kelley, Scott R.; Wolff, Bruce G.; Lovely, Jenna K.; Larson, David W.
Multimodal fast-track (FT) pathways for both open and laparoscopic colorectal surgery have been shown to improve gastrointestinal recovery, shorten length of stay, and decrease morbidity. The aim of our study was to determine if using alvimopan (Entereg)™ in the setting of a FT minimally invasive colorectal pathway is beneficial and cost-effective. All minimally invasive colorectal surgeries performed by one surgeon using a multimodal FT pathway with and without alvimopan were reviewed. Ninety total patients were identified, 64 patients treated without and 26 with alvimopan. Main outcomes included postoperative day tolerating a soft diet, return of gastrointestinal function, length of stay, 30-day readmission rate, and patient care, anesthesia, pharmacy, and combined cost. Tolerance of a soft diet, return of gastrointestinal function, and length of stay were all shorter and showed significance in the alvimopan group (mean 2.1 vs 2.8 days, mean 1.5 vs 2.4 days, and mean 3.5 vs 4.5 days, respectively) ( P = 0.0197, P = 0.0029, and 0.0158, respectively). Patient care and combined hospital costs were both increased in the nonalvimopan group; however, combined hospital costs was not significant ( P = 0.0216 and P = 0.0875, respectively). The 30-day readmission rate of 6.3 per cent was also not significant in this group ( P = 0.0941). Patients undergoing minimally invasive colorectal surgery treated with a multimodal FT pathway tolerated a soft diet sooner, had earlier return of bowel function, a shorter length of stay, and lower patient care and combined costs when alvimopan was used.